2021
DOI: 10.1101/2021.02.07.430110
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Resolving the conflict between antibiotic production and rapid growth by recognition of peptidoglycan of susceptible competitors

Abstract: Microbial communities employ a variety of complex strategies to compete successfully against competitors sharing their niche, with antibiotic production being a common strategy of aggression. Here, by systematic evaluation of four non-ribosomal peptides (NRP) produced by B. subtilis clade, we revealed that they acted either synergistically or additively to effectively eliminate phylogenetically distinct competitors. All four major NRP biosynthetic clusters were also imperative for the survival of B. subtilis i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 79 publications
(92 reference statements)
1
5
0
Order By: Relevance
“…B. subtilis was fully resistant to its own conditioned medium, B. atrophaeus was resistant to low concentrations of, but vulnerable to high concentrations of the conditioned medium, (50%v/v., p value<0.0001) and B. mycoides was sensitive to all of the tested concentrations of conditioned medium (p=0.0006) (Figure 1). These results are consistent with our previous work where we reported that the conditioned rich medium of B. subtilis pellicles was inert to self, slightly toxic to the related B. atrophaeus, and significantly toxic to B. mycoides [38].…”
Section: Conditioned Medium From B Subtilis Pellicles Is Selectively Toxic Towards Potential Competitorssupporting
confidence: 93%
See 4 more Smart Citations
“…B. subtilis was fully resistant to its own conditioned medium, B. atrophaeus was resistant to low concentrations of, but vulnerable to high concentrations of the conditioned medium, (50%v/v., p value<0.0001) and B. mycoides was sensitive to all of the tested concentrations of conditioned medium (p=0.0006) (Figure 1). These results are consistent with our previous work where we reported that the conditioned rich medium of B. subtilis pellicles was inert to self, slightly toxic to the related B. atrophaeus, and significantly toxic to B. mycoides [38].…”
Section: Conditioned Medium From B Subtilis Pellicles Is Selectively Toxic Towards Potential Competitorssupporting
confidence: 93%
“…Here we report that in addition to their structural role, manifested by their necessity for B. subtilis to generate pellicles (floating biofilms) with itself [57] and with a related bacterium, B. atrophaeus (Figure 1), the exopolysaccharides act to induce the production of bacillaene, a polyketide antibiotic [33,[58][59][60] which was recently shown to be essential for the elimination of phylogenetically distinct Bacillus species [38,61]. Our results indicate that this non-structural role of the exopolysaccharides is manifested by a capacity of B. subtilis to repel the phylogenetically distinct competitor, B. mycoides from the pellicle and its surrounding media.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations